2020
DOI: 10.5853/jos.2019.02845
|View full text |Cite
|
Sign up to set email alerts
|

Serum Neurofilament Light Chain Is Associated with Incident Lacunes in Progressive Cerebral Small Vessel Disease

Abstract: Background and Purpose Serum neurofilament light (NfL)-chain is a circulating marker for neuroaxonal injury and is also associated with severity of cerebral small vessel disease (SVD) cross-sectionally. Here we explored the association of serum-NfL with imaging and cognitive measures in SVD longitudinally.Methods From 503 subjects with SVD, baseline and follow-up magnetic resonance imaging (MRI) was available for 264 participants (follow-up 8.7±0.2 years). Baseline serum-NfL was measured by an ultrasensitive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 26 publications
5
36
2
1
Order By: Relevance
“…21 It is also broadly consistent with recent evidence in mild SVD showing baseline NfL predicts risk of future lacunes. 24 Why there was no significant change in NfL over 3 years in SCANS is uncertain and may be explained by dynamic changes in NfL post stroke. 25 26 Findings from patients with small subcortical infarcts demonstrated that NfL was elevated but eventually returned to normal levels after 15 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 It is also broadly consistent with recent evidence in mild SVD showing baseline NfL predicts risk of future lacunes. 24 Why there was no significant change in NfL over 3 years in SCANS is uncertain and may be explained by dynamic changes in NfL post stroke. 25 26 Findings from patients with small subcortical infarcts demonstrated that NfL was elevated but eventually returned to normal levels after 15 months.…”
Section: Discussionmentioning
confidence: 99%
“… 21 It is also broadly consistent with recent evidence in mild SVD showing baseline NfL predicts risk of future lacunes. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum NfL levels at 6 months after stroke positively correlate with an MRI‐based quantitative measure of secondary neurodegeneration [12]. As an association between plasma NfL levels and time since stroke was not found, the elevated plasma NfL levels in our study population conceivably reflect stroke‐induced secondary neurodegeneration, as well as age‐related changes in the white matter and other ongoing neurodegenerative processes such as those leading to Alzheimer's disease [21], or small vessel disease [22,23].…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, NfL data have also been recently obtained in cerebrovascular disease forms that are occasionally associated with a rapid course, such as small vessel disease. Here, blood NfL concentrations have been associated with disability and neurological symptoms, including future cognitive impairment (Gattringer et al, 2017;Duering et al, 2018;Peters et al, 2020). Moreover, the marker correlated with disease severity, disease progression, and survival in CADASIL patients (Gravesteijn et al, 2018).…”
Section: Autoimmune Encephalitis and Other Potentially Treatable Causmentioning
confidence: 94%